HUBUNGAN PERENCANAAN DAN PARTISIPASI MASYARAKAT DENGAN KEBERHASILAN PEMBANGUNAN DI DESA LOMPAD KECAMATAN RANOYAPO - Rantung, Rilia Lita; Posumah, Jhonny Hanny; Ogotan, Martha (Sam Ratulangi University, 2015)
Abstract: Basically national development is an effort to improve all aspects of society , the nation and thestate , which constitute the overall development process of the organization of the state system to achievenational goals. The problems in question in this research is how the relationship of planning andcommunity participation with the successful development in the village of the District Lompad Ranoyapo.The method used in this research is quantitative method . The study subjects were community Lompadvillage . The study sample was taken as many as 38 people . Data collection is done by using aquestionnaire . Data analysis technique used is the Multiple Regression Analysis with MultipleCorrelation Analysis.Data analysis showed that the regression coefficient of variable plan (X1) and participation (X2) with thesuccessful development of (Y) is positive and real and multiple correlation coefficients and determinationat the high category.Based on these results we can conclude that planning and community participation in rural developmentsufficient to show significant results, and there is a real relationship between community participationwith the successful development of the District Ranoyapo Lompad In the village.Based on these conclusions then suggest: (1) The village government should involve all elements of societyin implementing the Rural Development Planning function. (2) The government should encourage theparticipation of village communities to be involved in the implementation process of development of allaspects of the planning and to the evaluation and maintenance of rural development.Keyword : Planning , Participation Society, success of Development